Abrupt tropical climate change: past and present - Thompson, L. G.; Mosley-Thompson, E.; Brecher, H.; Davis, M.; Leon, B.; Les, D.; Lin, P. N.; Mashiotta, T.; Mountain, K. (Proc Natl Acad Sci U S A, 2006)
Three lines of evidence for abrupt tropical climate change, both past and present, are presented. First, annually and decadally averaged delta(18)O and net mass-balance histories for the last 400 and 2,000 yr, respectively, demonstrate that the current warming at high elevations in the mid- to low latitudes is unprecedented for at least the last 2 millennia. Second, the continuing retreat of most mid- to low-latitude glaciers, many having persisted for thousands of years, signals a recent and abrupt change in the Earth's climate system. Finally, rooted, soft-bodied wetland plants, now exposed along the margins as the Quelccaya ice cap (Peru) retreats, have been radiocarbon dated and, when coupled with other widespread proxy evidence, provide strong evidence for an abrupt mid-Holocene climate event that marked the transition from early Holocene (pre-5,000-yr-B.P.) conditions to cooler, late Holocene (post-5,000-yr-B.P.) conditions. This abrupt event, approximately 5,200 yr ago, was widespread and spatially coherent through much of the tropics and was coincident with structural changes in several civilizations. These three lines of evidence argue that the present warming and associated glacier retreat are unprecedented in some areas for at least 5,200 yr. The ongoing global-scale, rapid retreat of mountain glaciers is not only contributing to global sea-level rise but also threatening freshwater supplies in many of the world's most populous regions.
Thompson, Lonnie GMosley-Thompson, EllenBrecher, HenryDavis, MaryLeon, BlancaLes, DonLin, Ping-NanMashiotta, TracyMountain, KeithengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2006/07/04 09:00Proc Natl Acad Sci U S A. 2006 Jul 11;103(28):10536-43. Epub 2006 Jun 30.

A 17,000 year history of Andean climatic and vegetation change from Laguna de Chochos, Peru - Bush, M. B.; Hansen, B. C. S.; Rodbell, D. T.; Seltzer, G. O.; Young, K. R.; Leon, B.; Abbott, M. B.; Silman, M. R.; Gosling, W. D. (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice-accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global-scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm-dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500-yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600-yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape.
id: 1015